A kind of stone plastic floor and preparation method thereof

By using dry/semi-dry desulfurization ash to replace heavy calcium in stone plastic flooring, and combining it with modifiers, the problem of high density and warping of stone plastic flooring is solved, and the cost of transportation and production is reduced, and the amount of mining is reduced. Effect.

CN111395686BActive Publication Date: 2025-01-21FUJIAN LONGKING DSDN ENGINEERING CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010215005.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-03-24
Publication Date
2025-01-21
Estimated Expiration
2040-03-24

AI Technical Summary

Technical Problem

The stone plastic floor is dense and has high transportation costs during transportation, and the warping is high during use, which affects the paving effect.

Method used

Use dry/semi-dry desulfurization ash as a new filler to replace heavy calcium, and use modifiers with specific content components to reduce the density and warpage of stone plastic flooring.

Benefits of technology

On the basis of ensuring stable mechanical properties, it can effectively reduce the density and warpage of stone plastic flooring, reduce transportation costs and production costs, and reduce the mining volume of limestone mines, which has good social, economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111395686B_ABST
    Figure CN111395686B_ABST
Patent Text Reader

Abstract

The present invention provides a stone plastic floor, comprising: an SPC base layer; a color film layer attached to the SPC base layer; a wear-resistant layer attached to the color film layer; a UV layer composited on the wear-resistant layer; the SPC base layer is a PVC substrate layer filled with dry / semi-dry desulfurization ash. Compared with the prior art, the stone plastic floor provided by the present invention uses cheap dry / semi-dry desulfurization ash as a new type of filler to replace heavy calcium as a filler, and is matched with a modifier with a specific content component. On the basis of ensuring stable mechanical properties, it can effectively reduce the density and warping of the stone plastic floor at a relatively low cost, thereby effectively reducing the product transportation cost and improving the product stability; at the same time, the use of cheap dry / semi-dry desulfurization ash not only greatly reduces the production cost, but also realizes the comprehensive application of industrial solid waste, reduces the mining volume of limestone mines, and has good social benefits, economic benefits and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PVC flooring, and more specifically, to a stone plastic flooring and a preparation method thereof. Background Art

[0002] In recent years, the demand for PVC flooring has continued to increase, with the proportion increasing from 3% in 2014 to 7% in 2018. One of the most important products, stone plastic flooring, has developed rapidly. Since its official development and launch in 2017, stone plastic flooring has been quickly accepted by the market due to its advantages such as easy installation, a wide variety of patterns and colors, and no formaldehyde. It has been exported to European and American countries in large quantities and is in a stage of active promotion and rapid development in domestic and foreign markets. According to statistics, China's stone plastic flooring industry has developed rapidly since 2017, growing rapidly at a rate of 30% per year. In 2018, China's stone plastic flooring production was nearly 350 million m 2 , more than 70% are exported to Europe and the United States, with an export value of nearly 3.5 billion US dollars, and the consumption of heavy calcium is about 2.2 million tons. Domestic large developers such as Evergrande, Country Garden, Vanke and other merchants are gradually using stone plastic flooring to replace laminate flooring and multi-layer wood flooring as the floor material of fine decoration houses, and the future application prospects are huge.

[0003] The main problems faced by stone plastic flooring are high transportation costs and high warping during use, which is often close to 1mm. Stone plastic flooring is almost always shipped to Europe and the United States in the form of shipping containers, and there are strict total weight regulations for container loading. Because stone plastic flooring is added with heavy calcium (heavy calcium powder particles are dense, and the bulk density can reach 1.2g / cm 3 ) ratio can reach up to 78%, so the density is relatively high, close to 2.2kg / cm 3 , resulting in the existing container volume utilization rate of less than 50%, and high transportation costs; and by adding foaming agents, reducing the amount of heavy calcium added, etc., the mechanical properties of the stone plastic floor will be affected. In addition, the current stone plastic floor is mainly spliced ​​with locks, without glue bonding, and has high requirements for dimensional stability. The warping caused by the change of floor size under high and low temperatures (the existing production process still has a certain internal stress in the board after multiple rounds of roller pressing that cannot be completely eliminated) directly affects the floor paving effect. Excessive warping will cause the floor to bulge and deform, the splicing seam will become larger, and the floor will become loose.

[0004] At the same time, the largest consumption of heavy calcium in the SPC flooring industry comes from non-renewable limestone, which needs to be crushed and ground. Due to the uneven distribution of resources in my country, limestone resources are scarce in many SPC flooring production areas. The state vigorously regulates mining, and the approval procedures for limestone mining rights are more stringent. The price of heavy calcium continues to rise, and the production cost of SPC flooring continues to increase. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a stone plastic floor and a preparation method thereof. The stone plastic floor provided by the present invention adopts dry / semi-dry desulfurization ash as a new filler, which can effectively reduce the density and warping of the stone plastic floor while ensuring the stability of mechanical properties, and can greatly reduce the cost of raw materials, thereby having good social, economic and environmental benefits.

[0006] The present invention provides a stone plastic floor, comprising:

[0007] SPC base;

[0008] A color film layer attached to the SPC base layer;

[0009] A wear-resistant layer attached to the color film layer;

[0010] The UV layer is compounded on the wear-resistant layer; the SPC base layer is a PVC base layer filled with dry / semi-dry desulfurization ash.

[0011] Preferably, the dry / semi-dry desulfurization ash-filled PVC substrate layer is prepared from raw materials including the following components:

[0012] 100 to 120 parts by weight of PVC resin powder;

[0013] 300 to 400 parts by weight of dry / semi-dry desulfurization ash;

[0014] Desulfurization ash modifier 0-30 parts by weight;

[0015] 28 to 48 parts by weight of processing aids.

[0016] Preferably, the particle size D of the dry / semi-dry desulfurization ash is 90 <100μm, moisture content <2.0%.

[0017] Preferably, the desulfurized ash modifier comprises a first modifier and a second modifier; the first modifier is selected from one or more of polyethylene wax, oxidized polyethylene wax and low molecular weight polypropylene; the second modifier is selected from one or more of fatty acid salts, fatty acid amines and fatty acid esters.

[0018] Preferably, the processing aid comprises the following components:

[0019] 6 to 12 parts by weight of calcium stearate;

[0020] 6 to 12 parts by weight of chlorinated polyethylene;

[0021] Acrylate 6 to 9 parts by weight;

[0022] 8 to 10 parts by weight of stearic acid;

[0023] 2 to 5 parts by weight of polyethylene wax.

[0024] Preferably, the preparation method of the dry / semi-dry desulfurization ash-filled PVC substrate layer is specifically as follows:

[0025] a) modifying the dry desulfurization ash with a desulfurization ash modifier, and then sequentially adding PVC resin powder and a processing aid to mix them to obtain an SPC base mixture;

[0026] b) The SPC base layer mixture obtained in step a) is heated and blended by a twin-screw extruder and then extruded to obtain a dry / semi-dry desulfurization ash-filled PVC base layer after molding.

[0027] Preferably, the mixing method in step a) is high-speed stirring; the rotation speed of the high-speed stirring is 1000rpm to 20000rpm, and the auxiliary heating temperature is 60°C to 100°C.

[0028] Preferably, the temperature of the heating and blending in step b) is 180° C. to 220° C.; and the discharge speed of the extrusion is 2.5 m / min to 3.5 m / min.

[0029] The present invention also provides a method for preparing a stone plastic floor, comprising the following steps:

[0030] A color film layer and a wear-resistant layer are sequentially placed on the SPC base layer for heat bonding, and then subjected to UV coating treatment to form a UV layer on the wear-resistant layer to obtain a stone plastic floor; the SPC base layer is a PVC base material layer filled with dry / semi-dry desulfurization ash.

[0031] Preferably, the temperature of the thermal bonding is 90°C to 120°C.

[0032] The present invention provides a stone plastic floor, comprising: an SPC base layer; a color film layer attached to the SPC base layer; a wear-resistant layer attached to the color film layer; a UV layer composited on the wear-resistant layer; the SPC base layer is a PVC substrate layer filled with dry / semi-dry desulfurization ash. Compared with the prior art, the stone plastic floor provided by the present invention uses cheap dry / semi-dry desulfurization ash as a new type of filler to replace heavy calcium as a filler, and is matched with a modifier with a specific content component. On the basis of ensuring stable mechanical properties, it can effectively reduce the density and warping of the stone plastic floor at a relatively low cost, thereby effectively reducing the product transportation cost and improving the product stability; at the same time, the use of cheap dry / semi-dry desulfurization ash not only greatly reduces the production cost, but also realizes the comprehensive application of industrial solid waste, reduces the mining volume of limestone mines, and has good social benefits, economic benefits and environmental benefits.

[0033] In addition, the preparation method provided by the present invention has simple process, is easy to control, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A schematic diagram of the structure of the stone plastic floor provided by the present invention;

[0035] Figure 2 This is a schematic diagram of the structure of the stone plastic floor provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention provides a stone plastic floor, comprising:

[0038] SPC base;

[0039] A color film layer attached to the SPC base layer;

[0040] A wear-resistant layer attached to the color film layer;

[0041] The UV layer is compounded on the wear-resistant layer; the SPC base layer is a PVC base layer filled with dry / semi-dry desulfurization ash.

[0042] See also Figure 1 , Figure 1 The schematic diagram of the structure of the stone plastic floor provided by the present invention; wherein 1 is the SPC base layer, 2 is the color film layer, 3 is the wear-resistant layer, and 4 is the UV layer.

[0043] In the present invention, the SPC base layer is a PVC base layer filled with dry / semi-dry desulfurization ash. The thickness of the SPC base layer is preferably 1 mm to 10 mm, more preferably 3 mm to 6 mm.

[0044] In the present invention, the dry / semi-dry desulfurization ash-filled PVC substrate layer is preferably prepared from raw materials including the following components:

[0045] 100 to 120 parts by weight of PVC resin powder;

[0046] 300 to 400 parts by weight of dry / semi-dry desulfurization ash;

[0047] Desulfurization ash modifier 0-30 parts by weight;

[0048] 28 to 48 parts by weight of processing aid;

[0049] More preferably:

[0050] 100 parts by weight of PVC resin powder;

[0051] 300 to 350 parts by weight of dry / semi-dry desulfurization ash;

[0052] 6 to 11 parts by weight of desulfurized ash modifier;

[0053] 41 to 45 parts by weight of processing aids.

[0054] The present invention has no special restriction on the source of the PVC resin powder, and commercially available products well known to those skilled in the art can be used.

[0055] In the present invention, the dry / semi-dry desulfurization ash is a calcium-based powdered mixture rich in calcium sulfite produced by dry / semi-dry desulfurization processes such as circulating fluidized bed (CFB), NID or SDA (formed by reaction under the violently disturbed bed layer of the circulating fluidized bed). It is a kind of dry, fine-particle, loose general industrial solid waste powder material, the main components of which are calcium-based substances such as calcium sulfite, calcium sulfate, calcium carbonate, and calcium hydroxide; preferably dry desulfurization ash. In the present invention, the particle size D of the dry / semi-dry desulfurization ash is 90 Preferably <100 μm, and the moisture content is preferably <2.0%.

[0056] The present invention adopts cheap dry / semi-dry desulfurization ash as a new type of filler to replace heavy calcium as a filler; firstly, the calcium carbonate contained in the desulfurization ash has similar physical and chemical properties to heavy calcium, and calcium sulfite has good compatibility with high molecular substances such as PVC and stable chemical properties, so it is suitable for use in calcium plastic board as an inorganic filler. Calcium hydroxide can be used as a filler in PVC products to improve the thermal stability of the matrix, thereby reducing the warping of the board; secondly, due to the loose structure of the desulfurization ash particles, the bulk density is less than that of heavy calcium (the bulk density of dry / semi-dry desulfurization ash is 0.7g / cm 3 ~0.8g / cm 3 ), after being treated with a modifier, some holes can be wrapped and closed to form closed pores, which reduces the oil absorption value of desulfurization ash, making the processing fluidity of dry / semi-dry desulfurization ash equivalent to that of heavy calcium, and making the final density of the stone plastic floor less than that of the stone plastic floor filled with heavy calcium; therefore, the treated dry / semi-dry desulfurization ash can replace the heavy calcium used in the stone plastic floor, effectively reducing the density and warping of the stone plastic floor. At the same time, as the country's "winning the battle to protect the blue sky" continues to advance in depth, the number of devices using dry / semi-dry desulfurization systems has approached thousands, and the output of dry / semi-dry desulfurization ash is close to 60 million tons / year, which can fully meet the demand for stone plastic flooring; after replacing heavy calcium on a large scale, the mining volume of limestone mines can be significantly reduced, reducing the damage to the environment caused by mining.

[0057] In the present invention, the desulfurization ash modifier preferably includes a first modifier and a second modifier; wherein the first modifier is preferably selected from one or more of polyethylene wax, oxidized polyethylene wax and low molecular weight polypropylene, more preferably polyethylene wax or oxidized polyethylene wax; the second modifier is preferably selected from one or more of fatty acid salts, fatty acid amines and fatty acid esters, more preferably one or two of fatty acid amines and fatty acid esters. The present invention has no special restrictions on the source of the desulfurization ash modifier, and adopts a combination of commercially available products of the above-mentioned fatty acid salts, fatty acid amines, fatty acid esters, polyethylene wax, oxidized polyethylene wax and low molecular weight polypropylene that are well known to those skilled in the art. The present invention preferably first modifies the dry / semi-dry desulfurization ash by the first modifier, and then modifies the dry / semi-dry desulfurization ash by the second modifier, which is beneficial to improve the modification effect of the dry / semi-dry desulfurization ash.

[0058] In the present invention, the amount of the first modifier is preferably 0 to 15 parts by weight, more preferably 2 to 5 parts by weight; the amount of the second modifier is preferably 0 to 15 parts by weight, more preferably 4 to 6 parts by weight.

[0059] In the present invention, the processing aid preferably includes the following components:

[0060] 6 to 12 parts by weight of calcium stearate;

[0061] 6 to 12 parts by weight of chlorinated polyethylene;

[0062] Acrylate 6 to 9 parts by weight;

[0063] 8 to 10 parts by weight of stearic acid;

[0064] 2 to 5 parts by weight of polyethylene wax;

[0065] More preferably:

[0066] Calcium stearate 10 parts by weight;

[0067] 12 parts by weight of chlorinated polyethylene;

[0068] Acrylate 6 parts by weight;

[0069] 10 to 12 parts by weight of stearic acid;

[0070] 3 to 5 parts by weight of polyethylene wax.

[0071] The present invention has no special restriction on the source of the processing aid, and the processing aid is a combination of commercially available products of calcium stearate, chlorinated polyethylene (CPE), acrylate (ACR), stearic acid and polyethylene wax (PE wax) well known to those skilled in the art.

[0072] In the present invention, the preparation method of the dry / semi-dry desulfurization ash-filled PVC substrate layer is preferably as follows:

[0073] a) modifying the dry desulfurization ash with a desulfurization ash modifier, and then sequentially adding PVC resin powder and a processing aid to mix them to obtain an SPC base mixture;

[0074] b) The SPC base layer mixture obtained in step a) is heated and blended by a twin-screw extruder and then extruded to obtain a dry / semi-dry desulfurization ash-filled PVC base layer after molding.

[0075] The present invention first modifies the dry desulfurization ash with a desulfurization ash modifier, then sequentially adds PVC resin powder and a processing aid to mix, thereby obtaining an SPC base mixture. In the present invention, the modification process is specifically as follows:

[0076] Add the dry / semi-dry desulfurization ash into a high-speed mixer and stir it. Set the speed of the high-speed mixer to 1000rpm~20000rpm, the auxiliary heating temperature to 60℃~100℃, and the stirring time to 4min~6min. Then add the first modifier and blend it with the above dry desulfurization ash for 4min~6min, then add the second modifier and continue blending for 5min~7min to complete the modification process.

[0077] In the present invention, the mixing method is preferably high-speed stirring, which is achieved by using a high-speed stirrer well known to those skilled in the art. In the present invention, the rotation speed of the high-speed stirring is preferably 1000 rpm to 20000 rpm, more preferably 1200 rpm to 10000 rpm; the auxiliary heating temperature of the high-speed stirring is preferably 60°C to 100°C, more preferably 80°C to 90°C.

[0078] In the present invention, the mixing process is preferably specifically as follows:

[0079] Add PVC resin powder to the modified dry / semi-dry desulfurization ash and blend for 6 minutes to 15 minutes, then add processing aids and continue mixing for 3 minutes to 10 minutes to obtain SPC base mixture;

[0080] More preferably:

[0081] PVC resin powder was added to the modified dry / semi-dry desulfurization ash and blended for 8 minutes, and then a processing aid was added and mixed for 5 minutes to obtain an SPC base mixture.

[0082] After obtaining the SPC base mixture, the present invention preferably further comprises cooling it to 45° C. to 55° C. and then storing it in a silo.

[0083] After obtaining the SPC base mixture, the present invention heats and blends the obtained SPC base mixture through a twin-screw extruder and then extrude it to obtain a dry / semi-dry desulfurization ash-filled PVC base layer after molding.

[0084] In the present invention, the SPC base mixture is fed to a twin-screw extruder through a screw feeder, and after being heated and blended by the screw, the material is extruded from the end of the twin-screw extruder; the temperature of the heating and blending is preferably 180°C to 220°C, more preferably 185°C to 212°C; the extrusion discharge speed is preferably 2.5m / min to 3.5m / min, more preferably 3m / min to 3.3m / min.

[0085] In the present invention, the molding method is preferably to enter a four-roll calender through a mold for molding; in addition, during the molding process, the color film layer and the wear-resistant layer can be further placed in the four-roll calender for simultaneous heat bonding to achieve assembly molding of the SPC base layer with the color film layer and the wear-resistant layer; wherein the first and second rollers of the four-roll calender are used for shaping and thickness determination to obtain an SPC base layer with a determined thickness and shape, and the third and fourth rollers are used for film laminating and embossing, so that the color film layer and the wear-resistant layer are simultaneously heat-bonded with the above-mentioned SPC base layer to obtain an embossed sheet. In the present invention, the temperature of the first roller is preferably 135°C to 160°C, more preferably 155°C, the temperature of the second roller is preferably 135°C to 160°C, more preferably 135°C; the temperature of the third roller is preferably 90°C to 120°C, more preferably 120°C; the temperature of the fourth roller is preferably 90°C to 120°C, more preferably 100°C; the speed of the roller is preferably 1.3rpm to 1.9rpm, more preferably 1.5rpm.

[0086] In the present invention, the color film layer is attached to the SPC base layer; the present invention has no special restrictions on the source of the color film layer, and a commercially available PVC color film layer well known to those skilled in the art can be used. In the present invention, the thickness of the color film layer is preferably 0.05 mm to 0.1 mm, and more preferably 0.06 mm to 0.08 mm.

[0087] In the present invention, the wear-resistant layer is attached to the color film layer; the present invention has no special restrictions on the source of the wear-resistant layer, and a commercially available PVC wear-resistant layer known to those skilled in the art can be used. In the present invention, the thickness of the wear-resistant layer is preferably 0.1 mm to 1 mm, and more preferably 0.2 mm to 0.8 mm.

[0088] In the present invention, the UV layer is compounded on the wear-resistant layer to protect the color film from fading. In the present invention, the UV layer is preferably formed by UV coating treatment.

[0089] In the present invention, an optional additional layer is preferably provided on one side of the SPC base layer of the stone plastic floor; a Cork layer, an EVA layer or an IXPE layer well known to those skilled in the art may be used.

[0090] The stone plastic floor provided by the present invention adopts inexpensive dry / semi-dry desulfurization ash as a new type of filler to replace heavy calcium as a filler, and is matched with a modifier with a specific content component. On the basis of ensuring stable mechanical properties, the density and warping of the stone plastic floor can be effectively reduced at a relatively low cost, thereby effectively reducing the product transportation cost and improving the product stability; at the same time, the selection of inexpensive dry / semi-dry desulfurization ash not only greatly reduces the production cost, but also realizes the comprehensive application of industrial solid waste, reduces the mining volume of limestone mines, and has good social benefits, economic benefits and environmental benefits.

[0091] The present invention also provides a method for preparing a stone plastic floor, comprising the following steps:

[0092] A color film layer and a wear-resistant layer are sequentially placed on the SPC base layer for heat bonding, and then subjected to UV coating treatment to form a UV layer on the wear-resistant layer to obtain a stone plastic floor; the SPC base layer is a PVC base material layer filled with dry / semi-dry desulfurization ash.

[0093] In the present invention, the heat bonding device is preferably a four-roll calender; the first and second rollers of the four-roll calender are used for shaping and thickness determination to obtain an SPC base layer with a determined thickness and shape, and the third and fourth rollers are used for film bonding and embossing, so that the color film layer and the wear-resistant layer are simultaneously heat bonded to the above-mentioned SPC base layer to obtain an embossed sheet. In the present invention, the temperature of the first roller is preferably 135°C to 160°C, more preferably 155°C, the temperature of the second roller is preferably 135°C to 160°C, more preferably 135°C; the temperature of the third roller is preferably 90°C to 120°C, more preferably 120°C; the temperature of the fourth roller is preferably 90°C to 120°C, more preferably 100°C; the speed of the roller is preferably 1.3rpm to 1.9rpm, more preferably 1.5rpm.

[0094] After obtaining the embossed sheet, the present invention preferably further comprises:

[0095] The embossed sheet is cut into sheets of a certain size as required by a traction machine. In the present invention, the speed of the traction machine is preferably 2.5 m / min to 4 m / min, more preferably 3.2 m / min to 3.5 m / min.

[0096] Afterwards, the present invention preferably air cools the above-mentioned board to room temperature, and then performs UV coating treatment to form a UV layer on the wear-resistant layer to obtain the stone plastic floor. In the present invention, the UV coating treatment device is preferably a UV coating machine. In the present invention, the process of the UV coating treatment is preferably specifically as follows:

[0097] The plate is placed in a UV coating machine, coated with varnish and then dried to form a UV layer; the transmission speed of the UV coating machine is preferably 10m / min to 25m / min, more preferably 20m / min.

[0098] Finally, the present invention preferably also includes:

[0099] The board with UV layer formed on the surface is sent to the slotting machine, and horizontal and vertical slots are made according to the product size requirements to obtain the stone plastic floor.

[0100] The preparation method provided by the invention has simple process, is easy to control and is suitable for large-scale industrial production.

[0101] The present invention provides a stone plastic floor, comprising: an SPC base layer; a color film layer attached to the SPC base layer; a wear-resistant layer attached to the color film layer; a UV layer composited on the wear-resistant layer; the SPC base layer is a PVC substrate layer filled with dry / semi-dry desulfurization ash. Compared with the prior art, the stone plastic floor provided by the present invention uses cheap dry / semi-dry desulfurization ash as a new type of filler to replace heavy calcium as a filler, and is matched with a modifier with a specific content component. On the basis of ensuring stable mechanical properties, it can effectively reduce the density and warping of the stone plastic floor at a relatively low cost, thereby effectively reducing the product transportation cost and improving the product stability; at the same time, the use of cheap dry / semi-dry desulfurization ash not only greatly reduces the production cost, but also realizes the comprehensive application of industrial solid waste, reduces the mining volume of limestone mines, and has good social benefits, economic benefits and environmental benefits.

[0102] In addition, the preparation method provided by the present invention has simple process, is easy to control, and is suitable for large-scale industrial production.

[0103] In order to further illustrate the present invention, the following examples are used to explain the present invention in detail. The dry desulfurization ash used in the following examples of the present invention comes from a sintering machine in a steel plant in Fujian Province, and the particle size D 90 <100μm, moisture content <2.0%, main components: calcium sulfite 48.57wt%, calcium hydroxide 13.54wt%, calcium carbonate 25.66wt%; the PVC resin powder used is commercially available SG-5 type PVC resin powder; the color film layer used is commercially available PVC color film layer; the wear-resistant layer used is commercially available PVC wear-resistant layer.

[0104] Example 1

[0105] (1) 300 parts by weight of dry desulfurization ash was added to a high-speed mixer for stirring, and the speed of the high-speed mixer was set to 2000 rpm, the auxiliary heating temperature was set to 85°C, and the stirring time was set to 5 min; then 2 parts by weight of polyethylene wax was added and blended with the above dry desulfurization ash for 5 min, and then 4 parts by weight of fatty acid ester was added and blended for 6 min, and then 100 parts by weight of PVC resin powder was added and blended for 8 min, and finally 41 parts by weight of processing aid (composed of 10 parts by weight of calcium stearate, 12 parts by weight of chlorinated polyethylene, 6 parts by weight of acrylate, 10 parts by weight of stearic acid and 3 parts by weight of polyethylene wax) was added and blended for 5 min to obtain an SPC base mixture; after cooling to 50°C, the mixture was placed in a silo for storage.

[0106] (2) The SPC base layer mixture obtained in step (1) is fed into a twin-screw extruder through a screw feeder for heating and blending and then extruding, wherein the maximum temperature of the twin-screw extruder is 210° C. and the discharge speed is 3 m / min; then the extruded material is passed through a mold into a four-roll calender for assembly and molding, wherein the mold temperature is 195° C. and the roller speed is 1.5 rpm. The first and second rollers of the four-roll calender are used for shaping and thickness determination to obtain an SPC base layer with a determined thickness and shape, wherein the temperature of the first roller is 155° C. and the temperature of the second roller is 135° C.; the third and fourth rollers of the four-roll calender are used for film lamination and embossing, so that the color film layer and the wear-resistant layer are simultaneously thermally laminated with the above-mentioned SPC base layer to obtain an embossed sheet, wherein the temperature of the third roller is 120° C. and the temperature of the fourth roller is 100° C.

[0107] (3) The embossed sheet obtained in step (2) is passed through a traction machine at a speed of 3.2 m / min, and is cut into sheets of certain size as required; after air cooling to room temperature, the sheet is placed in a UV coating machine, coated with varnish and then dried to form a UV layer, and the conveying speed of the UV coating machine is 20 m / min; finally, the sheet with the UV layer formed on the surface is sent to a slotting machine, and horizontal and vertical slots are made according to the product size requirements to obtain the stone plastic floor.

[0108] See the structural diagram of the stone plastic floor provided in Example 1 of the present invention. Figure 2 As shown, the thickness of the SPC base layer is 3.2mm~5.5mm, the thickness of the color film layer is 0.07mm, the thickness of the wear-resistant layer is 0.3mm~0.7mm, and the UV layer protects the color film from fading; and the optional additional layer can be Cork, EVA or IXPE, which is not reflected in the preparation method of Example 1.

[0109] The stone plastic floor prepared by the preparation method provided in Example 1 of the present invention was made into corresponding test standard shapes for various performance tests, and the results are shown in Table 1.

[0110] Example 2

[0111] (1) 330 parts by weight of dry desulfurization ash was added to a high-speed mixer for stirring, and the speed of the high-speed mixer was set to 2000 rpm, the auxiliary heating temperature was set to 85°C, and the stirring time was set to 5 min; then 6 parts by weight of oxidized polyethylene wax was added and blended with the above dry desulfurization ash for 5 min, and then 3 parts by weight of fatty acid ester and 2 parts by weight of fatty acid amine were added and mixed for 5 min, and then 100 parts by weight of PVC resin powder was added and blended for 8 min, and finally 45 parts by weight of processing aid (composed of 10 parts by weight of calcium stearate, 12 parts by weight of chlorinated polyethylene, 6 parts by weight of acrylate, 12 parts by weight of stearic acid and 5 parts by weight of polyethylene wax) was added and mixed for 5 min to obtain an SPC base mixture; after cooling to 50°C, the mixture was placed in a silo for storage.

[0112] (2) The SPC base layer mixture obtained in step (1) is fed into a twin-screw extruder through a screw feeder for heating and blending and then extruding, wherein the maximum temperature of the twin-screw extruder is 212° C. and the discharge speed is 3.3 m / min; then the extruded material is passed through a mold into a four-roll calender for assembly and molding, wherein the mold temperature is 196° C. and the roller speed is 1.6 rpm. The first and second rollers of the four-roll calender are used for shaping and thickness determination to obtain an SPC base layer with a determined thickness and shape, wherein the temperature of the first roller is 155° C. and the temperature of the second roller is 135° C.; the third and fourth rollers of the four-roll calender are used for film lamination and embossing, so that the color film layer and the wear-resistant layer are simultaneously thermally laminated with the above-mentioned SPC base layer to obtain an embossed sheet, wherein the temperature of the third roller is 120° C. and the temperature of the fourth roller is 100° C.

[0113] (3) The embossed sheet obtained in step (2) is passed through a traction machine at a speed of 3.5 m / min, and is cut into sheets of certain size as required; after air cooling to room temperature, the sheet is placed in a UV coating machine, coated with varnish and then dried to form a UV layer, and the conveying speed of the UV coating machine is 20 m / min; finally, the sheet with the UV layer formed on the surface is sent to a slotting machine, and horizontal and vertical slots are made according to the product size requirements to obtain the stone plastic floor.

[0114] Comparative Example 1

[0115] The stone plastic floor was prepared by the preparation method provided in Example 1, except that in step (1): 300 parts by weight of dry desulfurization ash was added to a high-speed mixer for stirring, the speed of the high-speed mixer was set to 2000 rpm, the auxiliary heating temperature was 85° C., and the stirring time was 5 min; then 100 parts by weight of PVC resin powder was added and blended with the dry desulfurization ash for 8 min, and finally 41 parts by weight of a processing aid (consisting of 10 parts by weight of calcium stearate, 12 parts by weight of chlorinated polyethylene, 6 parts by weight of acrylate, 10 parts by weight of stearic acid and 3 parts by weight of polyethylene wax) was added and mixed for 5 min to obtain an SPC base mixture; and the mixture was cooled to 50° C. and then stored in a silo.

[0116] Comparative Example 2

[0117] The stone plastic floor was prepared by the preparation method provided in Example 1, except that in step (1): 300 parts by weight of 325-mesh heavy calcium was added to a high-speed mixer for stirring, the speed of the high-speed mixer was set to 2000 rpm, the auxiliary heating temperature was 85° C., and the stirring time was 5 min; then 100 parts by weight of PVC resin powder was added and blended with the heavy calcium for 8 min, and finally 41 parts by weight of a processing aid (consisting of 10 parts by weight of calcium stearate, 12 parts by weight of chlorinated polyethylene, 6 parts by weight of acrylate, 10 parts by weight of stearic acid and 3 parts by weight of polyethylene wax) was added and mixed for 5 min to obtain an SPC base mixture; and the mixture was cooled to 50° C. and then stored in a silo.

[0118] Table 1 Performance test results of the stone plastic floor prepared by the preparation methods provided in Examples 1 to 2 and Comparative Examples 1 to 2

[0119]

[0120] As can be seen from Table 1, the preparation method provided by Examples 1 to 2 of the present invention uses inexpensive dry desulfurization ash as a new filler to replace heavy calcium as a filler, and is combined with a modifier with a specific content component. On the basis of ensuring the stability of mechanical properties, the density and warping of the stone plastic floor can be effectively reduced at a relatively low cost, thereby effectively reducing the product transportation cost and improving the product stability; at the same time, the use of inexpensive dry desulfurization ash not only greatly reduces the production cost, but also realizes the comprehensive application of industrial solid waste, reduces the mining volume of limestone mines, and has good social benefits, economic benefits and environmental benefits.

[0121] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A stone plastic floor, comprising: SPC base; A color film layer attached to the SPC base layer; A wear-resistant layer attached to the color film layer; A UV layer composited on the wear-resistant layer; The SPC base layer is a PVC base layer filled with dry / semi-dry desulfurization ash; The dry / semi-dry desulfurization ash-filled PVC substrate layer is prepared from raw materials including the following components: 100 to 120 parts by weight of PVC resin powder; 300 to 400 parts by weight of dry / semi-dry desulfurization ash; Desulfurization ash modifier 0-30 parts by weight; 28 to 48 parts by weight of processing aid; The desulfurized ash modifier includes a first modifier and a second modifier; the first modifier is selected from one or more of polyethylene wax, oxidized polyethylene wax and low molecular weight polypropylene; the second modifier is selected from one or more of fatty acid salts, fatty acid amines and fatty acid esters; The processing aid comprises the following components: 6 to 12 parts by weight of calcium stearate; 6 to 12 parts by weight of chlorinated polyethylene; Acrylate 6 to 9 parts by weight; 8 to 10 parts by weight of stearic acid; 2 to 5 parts by weight of polyethylene wax.

2. The stone plastic floor according to claim 1, characterized in that: The particle size D of the dry / semi-dry desulfurization ash 90 <100μm, moisture content <2.0%.

3. The stone plastic floor according to claim 1, characterized in that: The preparation method of the dry / semi-dry desulfurization ash-filled PVC substrate layer is specifically as follows: a) modifying the dry desulfurization ash with a desulfurization ash modifier, and then sequentially adding PVC resin powder and a processing aid to mix them to obtain an SPC base mixture; b) The SPC base layer mixture obtained in step a) is heated and blended by a twin-screw extruder and then extruded to obtain a dry / semi-dry desulfurization ash-filled PVC base layer after molding.

4. The stone plastic floor according to claim 3, characterized in that: The mixing method in step a) is high-speed stirring; the rotation speed of the high-speed stirring is 1000rpm to 20000rpm, and the auxiliary heating temperature is 60°C to 100°C.

5. The stone plastic floor according to claim 3, characterized in that: The temperature of the heating and blending in step b) is 180° C. to 220° C.; the discharge speed of the extrusion is 2.5 m / min to 3.5 m / min.

6. A method for preparing the stone plastic floor according to any one of claims 1 to 5, comprising the following steps: A color film layer and a wear-resistant layer are sequentially placed on the SPC base layer for heat bonding, and then subjected to UV coating treatment to form a UV layer on the wear-resistant layer to obtain a stone plastic floor; the SPC base layer is a PVC base material layer filled with dry / semi-dry desulfurization ash.

7. The preparation method according to claim 6, characterized in that: The temperature of the thermal bonding is 90°C to 120°C.

Citation Information

Patent Citations

  • High-stability stone-plastic floor and preparing method thereof

    CN110202900A

  • Stone-plastic floor

    CN211850585U